Neuroprotective Studies on Polygonum hydropiper L. Essential Oils Using Transgenic Animal Models - Tong, Xin; Li, Xiaoling; Ayaz, Muhammad; Ullah, Farhat; Sadiq, Abdul; Ovais, Muhammad; Shahid, Muhammad; Khayrullin, Mars; Hazrat, Ali (Frontiers in Pharmacology, 2021)
Polygonum hydropiper L. and related species are reported to possess neuroprotective potentials. In an attempt to validate its anti-Alzheimer’s potentials, leaf oils (Ph. Lo) were extensively evaluated in this study against several in vitro and in vivo models of Alzheimer’s disease. The Ph. Lo were tested against pathological targets of Alzheimer’s diseases (ADs). The in vitro and in vivo assays were done for cholinesterase inhibition, anti-radical properties and cognitive assessments using transgenic animal models. In preliminary cholinesterase inhibition assays, Ph. Lo were more active against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2-azinobis (3-ethylbenzthiazoline)-6-sulfonic acid (ABTS), and hydrogen peroxide (H2O2) radicals. Subsequently, Ph. Lo was evaluated for its effects on special memory, exploratory behavior, and coordination using shallow water maze (SWM), Y-maze, open filed, and balance beam tests. Animal pre-genotyping was done via polymerase chain reaction (PCR) to confirm amyloid precursor protein (APP) transgene, and after completion of drug therapy, brain homogenates from the cortex and hippocampus were evaluated for cholinesterase and free radical studies. In SWM task, disease control animals treated with 10 mg/kg of Ph. Lo for 5 days exhibited significant improvement in cognitive performance indicated by low escape times on 5th day compared with normal animals. In the Y-maze test, transgenic animals showed higher spontaneous alternation behavior than disease control animals and standard control group animals. Ph. Lo therapy has improved the exploratory behavior and declined anxiety behavior in diseased animals as accessed via open field test. Ph. Lo administration significantly augmented the motor and coordination abilities of transgenic animals when compared to other groups of animals and declined AChE, BChE activities as well as free radicals load in the cortex and hippocampus tissues. Based on our finding, it is concluded that Ph. Lo exhibit significant neuroprotective potentials preliminary due to their anti-radicals and cholinesterase inhibitory activities. Ph. Lo need further detailed studies as potential aromatherapy against neurodegenerative disorders.